Analisis Dampak Fintech terhadap Efisiensi Operasional dan Kinerja UMKM - Fitriani, Bela; Mansur Chadi Mursid (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims to explore the role of Financial Technology (Fintech) as a strategic tool in supporting the growth and development of the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia. Through the Literature Review method with a descriptive qualitative approach, this study analyses various literatures to understand the positive impact of Fintech on operational efficiency and capital accessibility for MSMEs. The study revealed that Fintech lending is able to expand MSMEs' access to financing, reduce transaction costs, and improve financial literacy among businesses. In addition, Fintech acts as a catalyst in building a more modern, innovative, and competitive business management system. This research is expected to provide strategic insights for MSME players, policy makers, and other stakeholders in optimising Fintech to support the sustainability and growth of the MSME sector in the digital era. With the right technological adaptation, MSMEs can maximise the potential of Fintech while expanding opportunities for growth in the future.